Anemia and Bone Marrow Suppression After Intra-Arterial Chemotherapy in Children With Retinoblastoma: A Retrospective Analysis - Zeng, Changjuan; Han, Minglei; Fan, Jiayan; He, Xiaoyu; Jia, Renbing; Li, Li; Wen, Xuyang; Song, Xuefei; Hou, Lili (Frontiers in Oncology, 2022)
Background: Retinoblastoma (Rb) is a common ocular malignant tumor in children. Intra-arterial chemotherapy (IAC) has been widely used in children with Rb and has achieved an ideal therapeutic effect. However, IAC shows side-effects, including anemia and bone marrow suppression, for which explicit evidence on risk factors is lacking. This study aimed to evaluate the covariates that may affect the occurrence of anemia and bone marrow suppression in children with Rb after IAC. Methods: Children with Rb admitted between May 2019 and January 2021 were included; the differences in the number of children with anemia and bone marrow suppression before and after IAC under different covariates were enumerated. We entered all potential impact factors into a generalized estimating equation (GEE) and constructed a multivariate regression model to explore the related covariates of anemia and bone marrow suppression after IAC. Results: Data of 286 children with Rb were retrospectively collected. After IAC, children with Rb had increased degrees of anemia (p<0.0001, chi-square test) and bone marrow suppression (p=0.0005, chi-square test). Moreover, the numbers of children with Rb who had an increased cross-level change in the degrees of anemia and bone marrow suppression were 82 (41.84%) and 66 (33.17%), respectively. Our model showed that the factors that affect anemic classification in children with Rb after IAC included chest circumference and the degree of bone marrow suppression before IAC, while, the factors that affect the degree of bone marrow suppression included the sheath model and chemotherapy drugs. The factors that affect anemic classification included the heparin applied, chest circumference, anemic classification, and degree of bone marrow suppression before IAC. Additionally, the factors that affect the level of bone marrow suppression included chemotherapy drugs and degree of bone marrow suppression before IAC. Conclusion: Children with Rb may have an increased risk of anemia and bone marrow suppression after IAC. According to the GEE, we generated predictive equations for predicting anemic classification and degree of bone marrow suppression, which can play a clinical guiding role for the prediction and timely control of anemia and bone marrow suppression after IAC.